The drought acclimation ability of in-vitro potato (Solanum tuberosum L.) Diamant variety cultured in sorbitol supplementing medium - Thi Thu Huong, Phung; Quynh Mai, Le (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Potato ( Solanum tuberosum L.) is one of the most important crops in the world, places in the fourth in production. Climate change, specially sea level rising and drought significantly reduce yield of crops, including potato. Many researches showed that some plant species have ability to acclimate to environment stresses. In this study, the drought acclimation, the increasing of drought tolerance in plant achieved after a period of time exposed to the lower level of drought stress, was evaluated on in-vitro potato Diamant variety explants. The shoots of potato were grown on medium containing different concentration of sorbitol for 7 days to be considered as drought acclimation explants. Then the explants were transferred to mediums with higher sorbitol concentrations for further 14 to 28 days. Initial results showed that 50 mM sorbitol in acclimation time seem increase drought tolerance of potato Diamant variety better than other testing conditions. In compare with non-acclimation explants, the acclimation explants had higher shoots, reduce less fresh and dry weight, increased more new shoots and new leaves and also accumulated more chlorophyll.